TAHAP PENGUASAAN KEMAHIRAN PEMIKIRAN KRITIS DALAM KALANGAN PELAJAR KEJURUTERAAN DAN HUBUNGANNYA DENGAN PENCAPAIAN PELAJAR - Amiruddin, Mohd Hasril; Wan Mamat, Wan Norehan; Rohanai, Reyan Healme (Online Journal for TVET Practitioners, 2018)
Critical thinking skills is a very important skill in all professions. This study aims to identify the level of critical thinking skills among engineering students and its relationship to student achievement. 317 engineering students comprising 151 males and 166 females’ ages from 19 to 26 years old from three engineering faculties at Universiti Tun Hussein Onn Malaysia (UTHM) involved in this study. The Malaysian Critical Thinking Skills Instrument - MyCT consists of 61 items. This survey conducted using the questionnaire. Data were analysed using SPSS version 16.0 with descriptive statistics focusing on mean, standard deviation and percentage. Inferential statistics involving Mann-Whitney U and Spearman’s Rho were used in this study. Research finding showed that the critical thinking level for engineering students in UTHM was intermediate. The analysis using Mann-Whitney U test showed that no significant differences in critical thinking skills (Reasoning, Analytical and logical, Disposition and Assumptions) between males and females. Spearman's Rho correlation analysis showed was have relation between the student’s CPA achievement with critical thinking skills (Reasoning, Analytical and logical, Disposition and Assumptions). However correlation coefficient value shows a very weak correlation. The results of the study give the implications that the teaching and learning methods of critical thinking must be put in practice and to be improved in order to increase students’ critical thinking potential.